Keabsahan Transaksi Jual Beli Rumah Ditinjau Dari Kitab Undang-Undang Hukum Perdata - Gradia Okultra Alba; Alan Siti Nurrizky (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2023)
Buying and selling is a legal relationship that has rights and obligations between the parties, including house buying and selling transactions through a House Sale and Purchase Agreement (PPJB) and Sale and Purchase Deed (AJB) carried out in front of a notary. The study has a goal, namely to find out and analyze the validity of buying and selling transactions of houses in the perspective of the Civil Code. Juridical-normatic is used as a research method whose approach is in the form of laws and literature studies. The result of this study is a house sale and purchase agreement, namely a special agreement whose rules are contained in Article 1457 of the Civil Code. The validity of this sale and purchase refers to Article 1320 of the Civil Code concerning the legal terms of the agreement. Buying and selling houses is carried out through various stages, namely the preparation of PPJB, payment of seller and buyer taxes and the process of transferring the name in AJB before a notary. Legitimacy can occur if the making of this agreement is not because there is a forced withdrawal from any party,, does not violate the provisions of laws and regalutions, decency and the public interest.